Propellant Mass Gauging via Modal Analysis on the International Space Station - Peterson, Taylor (Proceedings of the Wisconsin Space Conference, 2022)
In order for NASA to obtain sustained human presence in space, a higher fuel gauging accuracy is required. Current gauging methods have a sub 5-10% error which requires an additional fuel margin for any rocket or satellite. Doing this increases weight, therefore creating a higher cost. Gauging technologies capable of solving this problem either do not exist or only exist at low Technology Readiness Levels (TRLs). The Modal Propellant Gauging (MPG) project is an effort to develop a higher resolution, light-weight, and cost efficient fuel gauging method for low-gravity environments. MPG uses excited surface acoustic waves on the outside of the tank to measure the tanks resonant frequencies. In microgravity, the liquid will adhere to and coat the inner walls of the tank. The resonant mode frequencies are sensitive to the presence of liquid, meaning the accuracy of MPG is amplified in low-gravity. Modal measurements are taken using sensors adhered to the outer tank walls and a small data acquisition system. A Frequency Response Function (FRF) is then generated to create a reading for a fuel gauge. The newest iteration of MPG is Modal Propellant Gauging - International Space Station (MPG-ISS), which will undergo 30 days of autonomous testing onboard the ISS. This payload will implement MPG onto two tanks separated into two ISS payload lockers. A set amount of liquid will be transferred between both tanks as data is taken on both and stored on the in-flight computer. The MPG-ISS experiment will help validate the use of MPG on future space mission, such as Artemis. This experiment is the next step for MPG to be used on future mission to the Moon and Mars.